Ministernotomy aortic valve surgery in patients with prior patent mammary artery grafts after coronary artery bypass grafting. (10th January 2019) - Orlov, Oleg I; Kaleda, Vasily I; Shah, Vishal N; Nguyen, Catherine; Orlov, Cinthia P; Sicouri, Serge; Takebe, Manabu; Goldman, Scott M; Plestis, Konstadinos A
Abstract: OBJECTIVES: Patients with patent internal thoracic artery (ITA) grafts after prior coronary artery bypass grafting surgery who require aortic valve replacement (AVR) pose unique technical challenges for safe and optimal myocardial protection. The purpose of this study is to review our short- and long-term outcomes with redo minimally invasive AVR in patients with patent in situ ITA grafts. METHODS: From 2008 to 2016, 48 patients with at least 1 patent in situ mammary artery graft underwent minimally invasive AVR. Preoperative computed tomography was performed in all patients to evaluate the relationship of patent grafts to the sternum. Retrograde coronary sinus and pulmonary vent catheters were placed via the right internal jugular vein. The in situ ITA grafts were not clamped during AVR. Transverse aortotomy, taking care to avoid the grafts arising from the aorta, was performed to expose the aortic valve. RESULTS: The median age of the patients was 78 years [Quartile 1 (Q1)–Quartile 3 (Q3): 71–81]. Thirty-nine (81%) patients were men, and 46 (96%) patients had aortic stenosis. The median cardiopulmonary bypass and cross-clamp times were 124 (Q1–Q3: 108–164) and 92 (Q1–Q3: 83–116) min, respectively. Moderate hypothermia at 28–30°C was used in all patients. Most patients received cold blood cardioplegia with antegrade induction and continuous retrograde delivery. Four patients received only retrograde delivery due to some degree of aortic insufficiency. Thirty-day mortality was 4% (2 of 48 patients). There was no conversion to full sternotomy, and no reoperations were performed for postoperative bleeding or sternal wound infection. Excluding the 2 patients who died in the hospital, the median postoperative length of stay was 7 days (Q1–Q3: 5–8). Overall survival at 1, 5 and 10 years was 94%, 87% and 44%, respectively. CONCLUSIONS: Percutaneous retrograde cardioplegia combined with antegrade cardioplegia and moderate hypothermia, without interruption of ITA flow, is a safe and reliable strategy in patients with patent ITA grafts undergoing aortic valve replacement. This strategy combined with a minimally invasive approach may reduce surgical trauma, and is a safe and effective technique in these challenging patients.